Financial Acculturation: A Conceptual Framework for Understanding Cultural Fluency in High-Net-Worth Contexts - Amanda C M Craft (Journal of Financial Therapy, 2026)
This paper introduces the concept of financial acculturation to describe the psychosocial process by which individuals unfamiliar with high-net-worth (HNW) financial environments acquire the emotional, behavioral, and symbolic fluency required to navigate them. While much existing literature assumes that financial knowledge or access alone ensures confident participation in financial settings, this framework challenges that assumption by highlighting the identity tensions, social discomfort, and cultural disorientation that can accompany upward mobility. Drawing on Berry’s (1997) theory of acculturation and Bourdieu’s (1986) theory of capital, this study proposes a five-stage model: Exposure, Observation and Sensemaking, Identity Friction, Mimicry and Practice, and Embodiment. These maps show how individuals internalize and adapt to unfamiliar financial cultural norms. The model extends traditional accounts of financial socialization by focusing on class-coded, often unspoken aspects of HNW contexts. Although the framework is particularly relevant for first-generation wealth creators, inheritors, and those marrying into wealth, its application extends to anyone navigating significant economic class transitions. Practical implications for financial therapists and related professionals are discussed, along with suggestions for future scale development that could assist in assessing client progress. The model also identifies situations in which financial acculturation may be contraindicated, such as when identity-erasing code-switching, emotional masking, or adaptation undermines a client’s sense of authenticity.
Keywords: class mobility; cultural capital; financial acculturation; financial therapy; high-net-worth individuals; identity transition